2020
DOI: 10.17159/sajs.2020/7614
|View full text |Cite
|
Sign up to set email alerts
|

Statistical classification of South African seasonal divisions on the basis of daily temperature data

Abstract: Across South Africa, a wide range of activities is influenced by differences in seasonality. In a South African context, there is little consensus on the timing of seasonal boundaries. Inconsistency exists through the use of ad-hoc approaches to define seasonal boundaries across South Africa. In this paper, we present one of the very first uniform statistical classifications of South African seasonal divisions on the basis of daily temperature data. Daily maximum and minimum temperature data were obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Across South Africa, seasonality influences a wide range of activities that contribute largely to the economy; however, there is little consensus on the timing of seasonal boundaries [38][39][40][41][42][43]. This is due to the inconsistencies in different ad hoc approaches to defining seasonal boundaries across South Africa [44]. The NICD [7] states that for the past thirteen years, the South African flu season has lasted for approximately 19 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Across South Africa, seasonality influences a wide range of activities that contribute largely to the economy; however, there is little consensus on the timing of seasonal boundaries [38][39][40][41][42][43]. This is due to the inconsistencies in different ad hoc approaches to defining seasonal boundaries across South Africa [44]. The NICD [7] states that for the past thirteen years, the South African flu season has lasted for approximately 19 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the above findings, it is clear that the acute respiratory disease season is most intense during the winter season. Each province had different thresholds; however, all of them increased in the fall and winter based on Van der Walt and Fitchett's [44] seasons classification. These thresholds vary significantly across provinces.…”
Section: Discussionmentioning
confidence: 99%
“…This study examines and compares trends in extreme cold temperature indices on an annual and seasonal timescale. The seasons are defined according to the astronomical divisions: summer encompassing December through January, autumn spanning March through May, winter from June to August and spring from September to November (Van der Walt and Fitchett, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…It was decided to use the two available sioutas to collect PM samples for OC and EC analysis, as well as the health tests during this campaign. These summer sampling periods can be considered representative of summer, since a recent study indicated that October to March can be classified as summer months in South Africa ( Van der Walt and Fitchett, 2020).…”
Section: Sample Collectionmentioning
confidence: 99%